Analysis of the development and progression of carbon monoxide poisoning–related acute kidney injury according to the Kidney Disease Improving Global Outcomes (KDIGO) criteria. (3rd August 2018) - Kim, Youn-Jung; Sohn, Chang Hwan; Seo, Dong-Woo; Oh, Bum Jin; Lim, Kyoung Soo; Chang, Jai Won; Kim, Won Young
Abstract: Context: Acute kidney injury (AKI) can occur after carbon monoxide (CO) intoxication; however, limited data are available. This study aimed to evaluate the prognostic value of the development and progression of AKI in patients with acute CO poisoning. Materials and methods: We conducted a retrospective cohort study using a prospective registry of CO poisoning between January 2010 and December 2015. AKI was defined and classified according to the Kidney Disease Improving Global Outcomes (KDIGO) criteria. Multivariate logistic regression analysis was conducted to determine the association between AKI and adverse outcomes, defined as neurological deficits at discharge or 28-day mortality. Results: A total of 661 patients were evaluated. According to KDIGO criteria, 114 patients (17.2%) had AKI (initial: stage 1, 70.2%; stage 2, 26.3%; stage 3, 3.5%) on admission and 119 (18.0%) finally developed AKI during their hospital stay (maximum: stage 1, 68.9%; stage 2, 23.5%; stage 3, 7.6%). Almost all patients (99.2%) were diagnosed as having their highest KDIGO stage within three days (median, one day). AKI development was associated with adverse outcomes (odds ratio (OR) 17.53, 95% confidence interval 45.00–77.14). Both initial and maximum AKI stages demonstrated a stepwise increase of adjusted OR for adverse outcomes. AKI stage progression occurred in 8.4% of patients with AKI and was an independent factor for adverse outcomes. Conclusion: CO poisoning- related AKI occurred in 18% and was mostly detected within one day after CO intoxication. The development and progression of AKI had a strong association with adverse outcomes and deserve further prospective investigation.